Strong-motion accelerographs Early history. - Brady, A. Gerald
The structural design profession has long been interested in the design of structures to resist the strong horizontal shaking of the ground during potentially damaging earthquakes. Recordings of this ground motion have successfully provided the data on which building codes, design procedures and strong ground motion research are based. The object of this Historical Note is to chronicle the early development of strong ground motion accelerographs in the United States (the 1930s), Japan (the 1950s) and New Zealand (the 1960s)?accelerographs that recorded on photographic paper, waxed paper and film?and to describe the early processing of these analog records into digital form suitable for the emerging power of the digital computer. Ground accelerations and structural accelerations are now familiar concepts in seismic design and seismic engineering research, though many users may be unfamiliar with early efforts to identify them, record them and present them as useful data.
Keywords: Early accelerographs; Recordings; Processing